ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE TAHUN 2014-2016 - Orri Aflakul Uzlah, 14.05.52.0053; Wardjono, Wardjono (Students' Journal of Accounting and Banking, 2018)
Abstract This study was conducted to examine the analysis of factors that affect financial distress on manufacturing companies listed on the Stock Exchange in the period 2014-2016. The number of selected samples is 107 subjects determined using purposive sampling method. Data collection was done by documentation technique collected through IDX website and BEI Corner-Unisbank Stikubank (Unisbank). Analytical technique used is logistic regression. The results of the analysis show that profitability and leverage can affect financial distress, while board size, board size, institutional ownership, managerial ownership, and audit committee size are not able to influence financial distress. Keywords : Good Corporate Governance, Financial Ratio, Financial Distress